Evaluation of Posbindu cadres motivation in training participation at Buaran Health Center, Pekalongan Regency - Nurul Aktifah; Endah Winarni; Mariya Ulfa (Universitas Muhammadiyah Magelang, 2022)
Morbidity and mortality rates rise as a result of noncommunicable diseases (NCDs). The government's attention to NCDs is through the integrated development center (Posbindu). Posbindu's implementation, on the other hand, needs to be improved. The objective of this community service is to assess cadre motivation for training participation. The community service method is training through lectures and discussions. According to the findings, age characteristics of 36-45 years (63.6%), secondary school graduate education (43.8%), not working (77.8%), and 2-3 years of being a cadre (80%) affect cadres' high motivation to participate in training. The conclusion is that the motivation level is influenced by the characteristics of cadres.